1994
DOI: 10.1148/radiology.191.3.8184067
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged cervical lymph nodes at helical CT.

Abstract: The L/T at helical CT provide an accurate assessment of reactive versus malignant nodes in the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(52 citation statements)
references
References 0 publications
2
46
1
3
Order By: Relevance
“…Compared to conventional CT, the helical CT improved the spatial resolution of the images and could offer information on the nodes, such as nodal size and architectures (4,5). Both nodal size and nodal necrosis have been widely used as criteria for metastatic nodes (6,7). A recent study using the receiver operating characteristic (ROC) curve analysis demonstrated that the performance of CT in detecting metastatic nodes was moderate, with the minimum axis diameter being a better size criterion compared with the maximum axial diameter (8).…”
mentioning
confidence: 99%
“…Compared to conventional CT, the helical CT improved the spatial resolution of the images and could offer information on the nodes, such as nodal size and architectures (4,5). Both nodal size and nodal necrosis have been widely used as criteria for metastatic nodes (6,7). A recent study using the receiver operating characteristic (ROC) curve analysis demonstrated that the performance of CT in detecting metastatic nodes was moderate, with the minimum axis diameter being a better size criterion compared with the maximum axial diameter (8).…”
mentioning
confidence: 99%
“…2 Although lymph node biopsy is the final method* to differentiate between benign and malignant nodes, several investigations are known to be helpful, including ultrasound and CT of nodes. 3,4 In this study, by reviewing the histopathological results of 220 lymph node biopsies and correlating the result with clinical findings and simple investigations, we attempted to develop a model predicting nodal malignancy from the age and sex of the patient, consistency of lymph node, result of Mantoux test and abdominal ultrasound.…”
mentioning
confidence: 99%
“…In this study, MRI potential for diagnosis of cervical lymph node metastasis is equal to MDCT; the reason being diagnostic criteria used in the interpretation of CT and MR for lymph nodal metastases, which include any node greater than 10mm in maximum diameter, presence of central necrosis, indistinct nodal margins and loss of fatty hilum 13,14 . Various authors suggested different size criteria for staging lymph nodes with CT and MR imaging 24,25 . However, it is often diffi cult to distinguish reactive lymph node from metastatic ones using these criteria.…”
Section: Discussionmentioning
confidence: 99%